Lamivudine for chronic hepatitis B: a brief review - Palumbo,Emilio (2008)
Until recently, the only generally approved treatment for chronic hepatitis B was alpha-interferon; however, it gives only moderate efficacy in terms of sustained response (biochemical, virological and histological). In fact, only 20% to 40% of treated patients respond to therapy, with lower percentages (~ 10%) among patients infected with precore-mutant strains of HBV (HBeAb HBV-DNA positive). The FDA of the USA approved the use of lamivudine in adult patients affected by chronic hepatitis B in 1998. In this review, we focused on the pharmacokinetic and pharmacodynamic properties and efficacy and tolerability of lamivudine in the treatment of chronic hepatitis B cases that are both HBeAg and anti-HBe-positive.